Efficiency of consolidated banks in Asia a meta-frontier approach. - Cheng, Jueli. (2008)
Bank consolidation accelerated recently after the Asian financial crisis. As competition intensifies, banks have to be able to effectively compare its technical efficiency against its rivals to better understand its market position. However, since different countries have varying access to technology such cross-border comparisons are not conclusive if the banks are assumed to operate under a common technology.